2017
DOI: 10.1002/alr.21943
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory infiltrate and mucosal remodeling in chronic rhinosinusitis with and without polyps: structured histopathologic analysis

Abstract: Significant histopathologic differences were evident in patients with CRSwNP and CRSsNP. No single feature reliably differentiated between the 2 subtypes, underscoring the heterogeneity of CRS and limitation of this phenotypic classification system. Eosinophilic aggregates were associated with significantly worse disease, possibly signifying a unique subtype. Further studies are needed to understand the relationship of histopathologic features to disease outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
113
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(127 citation statements)
references
References 15 publications
11
113
3
Order By: Relevance
“…The airway remodeling was first described in the lower airway in asthma. Recently, a growing numbers of studies investigated tissue remodeling in CRS and found that CRS is also characterized by mucosa remodeling [3]. It was reported that mucosal hypertrophy, basement membrane thickening, fibrosis, subepithelial collagen deposition and angiogenesis are common forms of remodeling in CRS [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The airway remodeling was first described in the lower airway in asthma. Recently, a growing numbers of studies investigated tissue remodeling in CRS and found that CRS is also characterized by mucosa remodeling [3]. It was reported that mucosal hypertrophy, basement membrane thickening, fibrosis, subepithelial collagen deposition and angiogenesis are common forms of remodeling in CRS [3].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a growing numbers of studies investigated tissue remodeling in CRS and found that CRS is also characterized by mucosa remodeling [3]. It was reported that mucosal hypertrophy, basement membrane thickening, fibrosis, subepithelial collagen deposition and angiogenesis are common forms of remodeling in CRS [3]. These tissue remodeling changes in CRS could affect normal sinonasal physiology, increase duration of symptoms and enhance surgical difficulty [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As our knowledge of pathophysiology evolves, treatment protocols must be adjusted to address specific underlying disease processes. Therefore, there is a need to develop tools to assist clinical decision‐making based on objective evidence, such as histopathology . In routine practice today, histopathology on surgical samples offers limited information on the heterogeneous pathogenic mechanisms underlying different CRSwNP endotypes, but a potential role of structured histopathological profiling for CRSwNP has begun to attract attention .…”
Section: Introductionmentioning
confidence: 99%